Prophet of Messiah's advent an exposition of the book of Micah - Tatford, Frederick Albert, 1901- (Sussex, UK Prophetic Witness, 1974)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Micah -- commentaries